Pengaruh Corporate Governance, Leverage, Dan Capital Intensity Terhadap Tax Avoidance - -, Kusnadi; Afifah, Lulu (Universitas Malahayati, 2020)
Tax is an obligation to surrender a portion of the wealth that must be paid by each taxpayer bothindividual and business entity (company). The purpose of this study is to find out corporategovernance, leverage, capital intensity and sales growth towards tax avoidance. This research is amanufacturing company listed on the Indonesia Stock Exchange in 2014-2017. This study usespurposive sampling with several criteria so as to obtain a sample of 40 companies. The data used inthe form of secondary data derived from annual financial reports, while the data analysis techniquesused are descriptive statistics, classic assumption tests, multiple linear regression analysis, andhypothesis testing using EViews 0.8. The results of the study show that audit quality, leverage, andsales growth have a significant influence on tax avoidance. Whereas institutional ownership, board ofcommissioners, audit committee, and capital intensity do not have a significant effect on taxavoidance.Keywords: corporate governance, leverage, capital intensity, dan tax avoidance.